Congenital Factor XIII Deficiency With the Presence of Inhibitor: A Case Study. Issue 1 (January 2021) - Karaman, Serap; Akkaya, Emre; Genc, Sema; Bilgili, Fuat; Kendirci, Alper S.; Tugcu, Deniz; Unuvar, Aysegul; Karakas, Zeynep; Demirkol, Demet; Bayramoglu, Zuhal; Omer, Beyhan
Abstract : Coagulation factor XIII (FXIII) is a fibrin-stabilizing factor with additional roles in wound healing and interactions between the decidua and fetus. Congenital FXIII deficiency is rare bleeding disorder. Inhibitor development against FXIII in inherited FXIII deficency is also uncommon, but may cause severe, life-threatening bleeding. FXIII is the last step in the coagulation cascade with normal coagulation paramaters (PT, aPTT), the detection of inhibitor to FXIII is quite difficult. The treatment of inhibitor-positive congenital FXIII deficiency is challenging due to the lack of a role of by-pass agents such as FVII. The best known ways of treatment in these cases are the use of high-dose FXIII concentrates and immunosuppression. Herein, we report the management of postoperative bleeding diathesis in a patient with FXIII deficiency who developed inhibitors, and to follow the clinical course of the disease with FXIII concentrate and immunosuppression.